Normalizers for microRNA quantification in plasma of patients with vulvar intraepithelial neoplasia lesions and vulvar carcinoma - Kamil Zalewski; Marcin Misiek; Artur Kowalik; Elwira Bakuła-Zalewska; Janusz Kopczyński; Aleksandra Zielińska; Mariusz Bidziński; Jakub Radziszewski; Stanisław Góźdź; Magdalena Kowalewska (Tumor Biology)
The role of circulating microRNAs as a promising tool for diagnosing cancer and monitoring anticancer therapies has been widely studied in the past decades. To date, no suitable reference microRNAs for normalizing quantitative real-time polymerase chain reaction assays has been identified in vulvar intraepithelial neoplasia lesions and vulvar squamous cell carcinoma. The purpose of this study was to select appropriate references for gene expression studies in plasma of patients with these lesions. Expression levels of six microRNAs—hsa-miR-425-5p, hsa-miR-191-5p, hsa-miR-93-5p, hsa-miR-423-5p, hsa-miR-103a-3p, and hsa-miR-16-5p—were analyzed by quantitative reverse transcription polymerase chain reaction in plasma samples obtained from 17 patients with vulvar intraepithelial neoplasia lesion and 27 patients with vulvar squamous cell carcinoma. The expression stability of these candidate normalizers was assayed using geNorm algorithm. hsa-miR-93-5p was revealed as the most stably expressed reference in plasma samples of both vulvar intraepithelial neoplasia lesion and vulvar squamous cell carcinoma patients. The results pointed at hsa-miR-93-5p and hsa-miR-425-5p as microRNAs that retained the greatest robustness in plasma of vulvar intraepithelial neoplasia lesion and vulvar squamous cell carcinoma patients, respectively. Our work is the first report on reference microRNA selection for quantitative real-time polymerase chain reaction applications in vulvar intraepithelial neoplasia lesion and vulvar squamous cell carcinoma. The candidate microRNA stability values for the two types of lesions are provided and might serve for normalization of the future novel microRNA biomarkers in these rare entities.